2018
DOI: 10.3390/toxics6020029
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Induced Oxidative DNA Damage, Inflammation and Apoptosis in Rat’s Brain after Oral Exposure

Abstract: Growing evidences demonstrated that zinc oxide nanoparticles (ZnONPs) could reach the brain after oral ingestion; however, the “neurotoxicity of” ZnONPs after oral exposure has not been fully investigated. This study aimed to explore the “neurotoxicity of” ZnONPs (<100 nm) after oral exposure to two doses; 40 and 100 mg/kg for 24 h and 7 days. The exposure to 40 and 100 mg/kg of ZnONPs for 24 h did not elicit “neurotoxicity” compared to normal control. However, the daily exposure to both doses for 7 days cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 86 publications
3
53
1
Order By: Relevance
“…In addition, the study showed a significant increase in the cerebral levels of IFN-in the treated animals [27]. Oxidative stress was also attributed to adverse effects in brain tissue, such as increased inflammatory cytokines, DNA fragmentation and stimulation of apoptosis, in rats exposed orally for 7 days to ZnO NPs [149]. Chen et al observed in human brain microvascular endothelial cells that oxidative stress, manifested as decreased mitochondrial potential and decreased the expression of TJ proteins, is also induced by Al NPs [18].…”
Section: The Role Of Oxidative Stress In Nps-induced Toxicity and Dnamentioning
confidence: 88%
“…In addition, the study showed a significant increase in the cerebral levels of IFN-in the treated animals [27]. Oxidative stress was also attributed to adverse effects in brain tissue, such as increased inflammatory cytokines, DNA fragmentation and stimulation of apoptosis, in rats exposed orally for 7 days to ZnO NPs [149]. Chen et al observed in human brain microvascular endothelial cells that oxidative stress, manifested as decreased mitochondrial potential and decreased the expression of TJ proteins, is also induced by Al NPs [18].…”
Section: The Role Of Oxidative Stress In Nps-induced Toxicity and Dnamentioning
confidence: 88%
“…It has been proven that nanoparticles may cause some degree of damage to the blood-brain barrier leading to increased permeability and facilitating its penetration into the central nervous system (CNS) [185]. Similarly, AgNP and ZnONP toxicity was also associated with the accumulation of nanoparticles in the brain, responsible for some degree of neuroinflammation and neurodegeneration caused by ROS induced CNS injury [186].…”
Section: Neurotoxicitymentioning
confidence: 99%
“…On the other hand, there are several accurate statements, which are approving the apoptotic activity of ZnONPs due to their ability to increase the intracellular ROS levels . According to our findings and both Hala Attia et al and Masoud Negahdary researches indicating the impacts have ZnONPs on decreasing the cellular antioxidant enzymes (GSH, CAT, and SOD), we suggest the ZnONPs mechanism is based on their ability in inducing apoptosis by down‐regulating the antioxidant enzymes and thus disabling the cells in controlling the amounts of ROS in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%